The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1023/a:1005597902470
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: One of the major side effects of nonsteroidal antiinflammatory drugs, such as indomethacin, is gastropathy. The purpose of this study was to search for a therapeutic drug to prevent this side effect in vitro. We found that geranylgeranylacetone, a unique antiulcer drug with a heat-shock protein-inducing ability, protected cultured guinea pig gastric mucosal cells from cell damage caused by indomethacin. This cytoprotective effect of geranylgeranylacetone required concentrations of more than 10(-6) M and incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…We have also shown previously that GGA and low concentrations of ethanol also protected gastric mucosal cells from necrotic cell death induced by NSAIDs. 7) Furthermore, these HSP-inducers inhibited gastric stressor-induced apoptosis in gastric mucosal cells in primary culture. 16) Thus, it seems that preinduction of HSPs in gastric mucosal cells protects the cells from both necrotic and apoptotic cell death due to all of gastric stressors.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have also shown previously that GGA and low concentrations of ethanol also protected gastric mucosal cells from necrotic cell death induced by NSAIDs. 7) Furthermore, these HSP-inducers inhibited gastric stressor-induced apoptosis in gastric mucosal cells in primary culture. 16) Thus, it seems that preinduction of HSPs in gastric mucosal cells protects the cells from both necrotic and apoptotic cell death due to all of gastric stressors.…”
Section: Discussionmentioning
confidence: 95%
“…5) Using gastric mucosal cells in primary culture, we previously showed that pre-induction of HSPs makes cells resistant to necrotic cell death induced by NSAIDs. 7) Pre-induction of HSPs also makes cells resistant to cell death induced by ethanol. 6) We therefore examined here the effect of pre-induction of HSPs on necrotic cell death due to these gastric stressors, using GGA, an anti-ulcer drug with the capability of inducing HSP-expression.…”
Section: Effect Of Gga and Low Concentrations Of Ethanol On Necrosis mentioning
confidence: 99%
See 1 more Smart Citation
“…28,29) Isolated gastric mucosal cells were cultured for 12 h in RPMI 1640 containing 0.3% v/v FBS, 100 U/ml ampicillin and 100 mg/ml streptomycin in type-I collagen-coated plastic culture plates under the conditions of 5% CO 2 /95% air and 37°C. After removing non-adherent cells, cells attached to the plate were used.…”
Section: Methodsmentioning
confidence: 99%
“…2,3) We have also previously shown that endogenous factors that protect the gastric mucosa from such irritants (heat shock proteins (HSPs) and prostaglandins (PGs)) or anti-ulcer drugs suppress apoptosis and necrosis in this cell model. [4][5][6][7][8][9] This suggests that this in vitro system is useful for understanding the mechanisms underlying irritant-induced gastric lesions in vivo.…”
mentioning
confidence: 99%